Circulating Collagen Metabolites and the Enhanced Liver Fibrosis (ELF) Score as Fibrosis Markers in Systemic Sclerosis - Chen, Chen; Wang, Lingbiao; Wu, Jinfeng; Lu, Meijuan; Yang, Sen; Ye, Wenjing; Guan, Ming; Liang, Minrui; Zou, Hejian (Frontiers in Pharmacology, 2022)
Background: Serum fibrosis markers for systemic sclerosis (SSc) remain limited. The Enhanced Liver Fibrosis (ELF) score is a collagen marker set consisting of procollagen type III amino terminal propeptide (PIIINP), tissue inhibitor of metalloproteinases 1 (TIMP-1), and hyaluronic acid (HA). This longitudinal study aimed to examine the performance of the ELF score and its single analytes as surrogate outcome measures of fibrosis in SSc. Methods: Eighty-five SSc patients fulfilling the 2013 ACR/EULAR criteria with the absence of chronic liver diseases were enrolled. Serum PIIINP, TIMP-1, HA, and the ELF score were measured and correlated with clinical variables including the modified Rodnan skin score (mRSS) and interstitial lung disease (ILD). Twenty SSc patients underwent a follow-up serological testing and mRSS evaluation during treatment with immunosuppressants and/or anti-fibrotic drugs. Results: Serum PIIINP, TIMP-1, and ELF score were significantly higher in patients with SSc than in healthy controls [PIIINP: 10.31 (7.83–14.10) vs. 5.61 (4.69–6.30), p < .001; TIMP-1: 110.73 (66.21–192.45) vs. 61.81 (48.86–85.24), p < .001; ELF: 10.34 (9.91–10.86) vs. 9.68 (9.38–9.99), p < .001]. Even higher levels of PIIINP, TIMP-1, and ELF score were found in patients with diffuse cutaneous SSc than those with limited cutaneous SSc. At baseline, both PIIINP and ELF score showed good correlation with mRSS (PIIINP: r = .586, p < .001; ELF: r = .482, p < .001). Longitudinal analysis showed that change in PIIINP positively correlated with change in mRSS (r = 0.701, p = .001), while change in ELF score were not related, in a statistical context, to the change in mRSS (ELF: r = .140, p = .555). Serum TIMP-1 was significantly higher in SSc patients with ILD, compared to the matched group of patients without ILD [109.45 (93.05–200.09) vs. 65.50 (40.57–110.73), p = 0.007]. Conclusion: In patients with SSc, the ELF score well correlates with the extent of skin fibrosis, while serum PIIINP is a sensitive marker for longitudinal changes of skin fibrosis. In the future, circulating collagen metabolites may potentially be used to evaluate therapeutic effects of anti-fibrotic treatments in the disease.